Solasodine Induces Apoptosis, Affects Autophagy, and Attenuates Metastasis in Ovarian Cancer Cells - Xu, Xiao-Huang; Zhang, Le-Le; Wu, Guo-Sheng; Chen, Xin; Li, Ting; Chen, Xiuping; Wang, Yi-Tao; Lu, Jin-Jian (Planta Medica, 2017)
Solasodine, a steroidal alkaloid isolated from solanaceous species, exhibits anticancer activities on several cell lines. This study aimed to explore the antitumor potential of solasodine on ovarian cancer cells. The MTT assay, lactate dehydrogenase release assay, Hoechst 33342 staining, 5,5′,6,6′-tetrachloro-1,1′,3,3′-tetraethyl-imidacarbocyanine staining assay, and Annexin V/PI assay were conducted to investigate the antiproliferation and apoptosis-inducing effects of solasodine. Monodansylcadaverine staining was performed to label the acidic puncta on ovarian cancer HEY cells. A wound healing assay and Transwell assay were carried out to determine whether solasodine elicits an antimetastatic effect on HEY cells. A gelatin zymography assay was applied to detect the enzymatic activities of matrix metalloproteinases. Western blot was employed to examine relevant protein expression. Results revealed that solasodine inhibited cell viabilities in a time- and dose-dependent manner, triggered apoptotic body formation, reduced cell mitochondrial membrane potential, and interfered with autolysosome degradation in ovarian cancer cells. Solasodine also suppressed the migration and invasion of HEY cells by downregulating matrix metalloproteinase expression and activities. This study could be used as a basis for further studies on the molecular mechanisms of the antiproliferation, apoptosis-inducing, autophagy-modifying, and antimetastatic activities of solasodine.
Keywords: ovarian cancer; solasodine; apoptosis; autophagy; migration; invasion